Nuclear genomes of dinoflagellates reveal evolutionarily conserved pattern of RNA editing relative to stress response - Chen, Yibi; Dougan, Katherine E.; Bhattacharya, Debashish; Chan, Cheong Xin (Frontiers in Protistology, 2024)
Dinoflagellates are a group of diverse protists with complex genomes whose gene expression regulation mechanisms remain little known. RNA editing is a post-transcriptional regulatory mechanism of gene expression utilized by diverse species, and has been described primarily in the chloroplast and mitochondrial genomes of dinoflagellates. Its role in post-transcriptional regulation in the nuclear genomes of dinoflagellates remains largely unexplored. Here, integrating genome and transcriptome data from two dinoflagellate taxa in a comparative analysis, we identified 10,486 and 69,953 putative RNA editing sites in the nuclear genomes of the coral symbiont, Durusdinium trenchii CCMP2556 and the free-living bloom-forming taxon, Prorocentrum cordatum CCMP1329. We recovered all 12 possible types of RNA edits, with more edits representing transitions than transversions. In contrast to other eukaryotes, we found a dominance of A-to-T transversion in non-coding regions, many of which were condition-specific. Overall, the RNA editing sites implicate 7.5% of D. trenchii genes and 13.2% of P. cordatum genes. Some sites (1.5% in D. trenchii and more-substantially 62.3% in P. cordatum) were edited at significantly different frequencies in distinct growth conditions. The distribution of editing types and locations exhibited conserved patterns between the two phylogenetically distant species. Interestingly, A-to-T editing within the untranslated regions appear to be associated with upregulation of the edited genes in response to heat stress. These results lend support to the hypothesis that RNA editing is a key molecular mechanism that underpins regulation of gene expression in dinoflagellates.